2020
DOI: 10.1111/dmcn.14779
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socioeconomic status on cognitive outcome after childhood arterial ischemic stroke

Abstract: Aim To determine whether socioeconomic status (SES) is a stronger predictor for cognitive outcome after childhood arterial ischemic stroke compared to clinical factors. Method We investigated perceptual reasoning, executive functions, language, memory, and attention in 18 children and adolescents (12 males, six females, median age at testing 13y 4mo, range 7y–17y 5mo) after arterial ischemic stroke; collected sociodemographic information (education of parents, household income); and used clinical information (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…20 Additionally, childhood socioeconomic status is a strong predictor of child development, 21 and could explain up to 42% of the variance in developmental outcome after childhood arterial ischaemic stroke. 22 As anticipated, children included in our study exposed to perinatal inflammation had a lower median social status score than non-exposed children. Because of the strong association between social status and development, the higher median FSIQ score at 7 years of age in children exposed versus non-exposed to perinatal inflammation was unexpected.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…20 Additionally, childhood socioeconomic status is a strong predictor of child development, 21 and could explain up to 42% of the variance in developmental outcome after childhood arterial ischaemic stroke. 22 As anticipated, children included in our study exposed to perinatal inflammation had a lower median social status score than non-exposed children. Because of the strong association between social status and development, the higher median FSIQ score at 7 years of age in children exposed versus non-exposed to perinatal inflammation was unexpected.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, maternal inflammation was defined by a composite maternal pro‐inflammatory score, derived from the z‐scores of three cytokine serum concentrations: IL‐6, CRP, and TNF‐α 20 . Additionally, childhood socioeconomic status is a strong predictor of child development, 21 and could explain up to 42% of the variance in developmental outcome after childhood arterial ischaemic stroke 22 . As anticipated, children included in our study exposed to perinatal inflammation had a lower median social status score than non‐exposed children.…”
Section: Discussionmentioning
confidence: 99%
“…Educational levels were rated on a 7-point scale for the mother and the father separately, and the family household monthly gross net income was classified on an 11-point scale and rescaled to a 7-point scale. The socioeconomic status was calculated by taking the arithmetic mean of maternal education, paternal education, and household income (see Bartha-Doering et al 69 for more information on the questions and analyses).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between socioeconomic status and pediatric health has been well-documented over many years ( 34 ). One study found that socioeconomic status was a better predictor of cognitive outcome in childhood arterial ischemic stroke than clinical factors ( 35 ). For example, the financial situation of the family may affect the quantity and quality of treatment, and parental education may be linked to children's cognitive reserve.…”
Section: Factors Affecting Cognitive Impairmentmentioning
confidence: 99%